The impact of cancer drug wastage on economic evaluations. Issue 18 (22nd June 2017) - Truong, Judy; Cheung, Matthew C.; Mai, Helen; Letargo, Jessa; Chambers, Alexandra; Sabharwal, Mona; Trudeau, Maureen E.; Chan, Kelvin K. W.
Abstract : BACKGROUND: The objective of this study was to determine the impact of modeling cancer drug wastage in economic evaluations because wastage can result from single‐dose vials on account of body surface area– or weight‐based dosing. METHODS: Intravenous chemotherapy drugs were identified from the pan‐Canadian Oncology Drug Review (pCODR) program as of January 2015. Economic evaluations performed by drug manufacturers and pCODR were reviewed. Cost‐effectiveness analyses and budget impact analyses were conducted for no‐wastage and maximum‐wastage scenarios (ie, the entire unused portion of the vial was discarded at each infusion). Sensitivity analyses were performed for a range of body surface areas and weights. RESULTS: Twelve drugs used for 17 indications were analyzed. Wastage was reported (ie, assumptions were explicit) in 71% of the models and was incorporated into 53% by manufacturers; this resulted in a mean incremental cost‐effectiveness ratio increase of 6.1% (range, 1.3%‐14.6%). pCODR reported and incorporated wastage for 59% of the models, and this resulted in a mean incremental cost‐effectiveness ratio increase of 15.0% (range, 2.6%‐48.2%). In the maximum‐wastage scenario, there was a mean increase in the incremental cost‐effectiveness ratio of 24.0% (range, 0.0%‐97.2%), a mean increase in the 3‐year total incremental budget costs of 26.0% (range, 0.0%‐83.1%), and an increase in the 3‐year total incremental drug budget cost of approximately CaD 102 million nationally. Changing the mean body surface area or body weight caused 45% of the drugs to have a change in the vial size and/or quantity, and this resulted in increased drug costs. CONCLUSIONS: Cancer drug wastage can increase drug costs but is not uniformly modeled in economic evaluations. Cancer 2017;123:3583‐90. © 2017 American Cancer Society . Abstract : The wastage of anticancer drugs can have a significant impact on economic evaluation models according to this review of cost‐effectiveness analyses submitted by drug manufacturers to the pan‐Canadian Oncology Drug Review. The analysis shows that drug wastage increases incremental cost‐effectiveness ratios in submitted analyses by a mean of 24%, 3‐year total incremental costs by 26%, and total incremental drug budget costs by CaD 102 million nationally over a 3‐year period. Guidance for consistent and informed modeling of drug wastage in economic evaluations is warranted. See also pages 3445‐6.